Optimisation of Temperature Fields of Microsystems with Self-Organising Neural Nets - P. Bratek; A. Kos (Active and Passive Electronic Components)
Thermal modelling and optimisation of parameter distributed systems is a rather time-consuming process. In this paper the problem of optimisation of temperature fields of VLSI circuits and systems is attacked by a selforganising neural net. The net directly solves the task generated by a heuristic algorithm. No physical model of thermal phenomena is used. The proposed method is simple. Some examples and statistical results are presented. The proposed method is addressed mostly to large, high-speed system designs.